Misi Gereja dalam Mewujudkan Keadilan Sosial: Sebuah Perspektif dari Sila Kelima Pancasila - Piter Randan Bua; David Samiyono; Tony Christian Tampake (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2019)
This article aims to see the mission of the Gereja Kristen Indonesia (GKI Peterongan) in the perspective of the fifth principle of Pancasila namely social justice for all Indonesian people. Social justice in the perspective of the fifth principle of Pancasila is political justice and economic justice. Equally the same is based on the constitution and the same sense in the economic field. The meaning of social justice is built on the basis of kinship and mutual cooperation and all for all. The method used in this study uses qualitative methods through the study of documents, interviews and observations. In this study it was found that GKI Peterongan aspires to realize social justice for all people but has not been reflected and implemented in existing programs. In reality the implementation of the GKI Peterongan mission has not yet led to the realization of social justice for all Indonesian people. The mission of the GKI Peterongan is still exclusive and qualitative and has not given much thought to the community outside the church. Abstrak Artikel ini bertujuan melihat misi Gereja Kristen Indonesia Peterongan (GKI Peterongan) dalam perspektif Sila Kelima Pancasila yaitu Keadilan Sosial bagi seluruh rakyat Indonesia. Keadilan Sosial dalam perspektif Sila Kelima Pancasila adalah keadilan politik dan keadilan ekonomi. Sama – sama rata sama rasa berdasarkan konstitusi dan sama rata – sama rasa dalam lapangan ekonomi. Artinya keadilan sosial yang dibangun atas dasar kekeluargaan dan gotong royong serta semua untuk semua. Metode yang digunakan dalam penelitian ini menggunakan metode kualitatif melalui studi dokumen, wawancara dan observasi. Pada penelitian ini ditemukan bahwa GKI Peterongan bercita – cita mewujudkan keadilan sosial bagi seluruh rakyat namun belum tercermin dan terimplementasi dalam program – program. Kenyataannya pelaksanaan misi GKI Peterongan belum mengarah pada perwujudan keadilan sosial bagi seluruh rakyat Indonesia. Misi GKI Peterongan masih bersifat ekslusif dan karitatif serta belum banyak memikirkan masyarakat di luar gereja.